2020
DOI: 10.1039/c9ee04197d
|View full text |Cite
|
Sign up to set email alerts
|

Multiorbital bond formation for stable oxygen-redox reaction in battery electrodes

Abstract: Nonbonding oxygen 2p orbitals during oxygen-redox reaction are monitored using resonant inelastic X-ray scattering (RIXS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 51 publications
2
67
0
Order By: Relevance
“…In cases where the structure is preserved, it has been argued that localized oxygen holes relax by forming peroxo-like O-O bonds or by partial charge transfer to adjacent transition metals. 11, 46,48 We have shown that O-O distance shortening observed in Li 2 IrO 3 11 is a consequence of π-redox rather than independent O-O interactions. This behavior contrasts with that of sulfides, 49,50 where we find that structure-preserving anion redox through S-S dimerization is favored over π[S]-redox, as described in Supplementary Discussion 1.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…In cases where the structure is preserved, it has been argued that localized oxygen holes relax by forming peroxo-like O-O bonds or by partial charge transfer to adjacent transition metals. 11, 46,48 We have shown that O-O distance shortening observed in Li 2 IrO 3 11 is a consequence of π-redox rather than independent O-O interactions. This behavior contrasts with that of sulfides, 49,50 where we find that structure-preserving anion redox through S-S dimerization is favored over π[S]-redox, as described in Supplementary Discussion 1.…”
Section: Methodsmentioning
confidence: 88%
“…This behavior contrasts with that of sulfides, 49,50 where we find that structure-preserving anion redox through S-S dimerization is favored over π[S]-redox, as described in Supplementary Discussion 1. Finally, the apparent charge redistribution between transition metals and oxygen reported in a number of systems 46,48 is an artefact of the projection of the delocalized π-state onto atomic orbitals. We have shown that the key properties of the π-redox center arise from its delocalized, network structure and cannot be explained by a locally projected bonding model.…”
Section: Methodsmentioning
confidence: 99%
“…To monitor the detailed valence partial density of states (pDOS) of oxygen, resonant inelastic X-ray scattering (RIXS) spectra were measured using an incident photon of 531.5 eV. The emergence of a new emission peak at 523 eV in the RIXS spectrum for charged Na 2- x Mn 3 O 7 is typical for charged oxygen-redox electrodes 5 , 24 , 28 , 39 , 40 . Although O −• formation is implicated by the small voltage hysteresis in the charge/discharge processes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although O −• formation is implicated by the small voltage hysteresis in the charge/discharge processes (Fig. 2a ), the new inelastic scattering can be explained by either (1) energy loss from a π(Mn-O) → π * (Mn-O) transition (O −• formation), or (2) energy loss from a σ(O-O) → σ * (O-O) transition (peroxide-like O 2 2− formation) 40 . While observation of the new RIXS peak at 523 eV confirms the occurrence of the oxygen-redox reaction itself in Na 2- x Mn 3 O 7 , but this evidence alone does not definitely identify the reaction mechanism, or the chemical state of the oxidized oxygen species.…”
Section: Resultsmentioning
confidence: 99%
“…3d, higher temperatures lead to a larger production rates of CO 2 , which indicated fast and deep oxidation process of graphite into CO 2 at high temperatures. [37][38][39][40] Combining the XPS results, it can be induced that more oxygen-containing functional groups were further oxidized to CO 2 at high temperature, causing the decreasing oxygen content of products at high temperature. The above results also suggest that the products of anodic oxidation are dominated by oxygen-containing functional groups in 5-65 C range and by CO 2 in 65-95 C range.…”
Section: Anodic Oxidation and Its Dependence On Temperaturementioning
confidence: 97%